Фонды экономического стимулирования - Марченко Алексей Константинович (Экономические знания - всем, 1975)
Экземпляры: КХ (2024052) / Инвентарный номер: 0225577 / Сис.шифр: 338С / Авт.знак: М 30 / ГРНТИ: 06 / ББК: 65